(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
A new diapsid reptile is described from the locality of Cene (Seriana Valley, near Bergamo, Lombardy, Northern ltaly) from an outcrop of the Calcare di Zorzino (Zorzino Limestone) Formation (Middle Norian, Late Triassic). It is based on virtually identical specimens, differing only in size. Analysis of available diagnostic characters allows it to be included in the Prolacertiformes, represenring a new genus and species, Langobardisaurus pandolfi probably related to Macrocnemus, possibly to Cosesaurus, and to the Tanystropheidae. It is assumed here that Langobardisaurus pandolfii was adapted to a terrestrial mode of life and probably to an insectivorous diet.